Compulsory custody between Islamic texts and schools of Jurisprudence Critics and Analysis - Al-Hawrami, Asst. Prof. Dr. Adnan Abdul Qader Kamel Al-Hawrami; Abdullah, Asst.Prof.Dr. Kaml Aziz Abdullah; Mohammed, Asst. Prof. Dr. Ibrahim Abdel-Rahman Mohammed (Sulaimani Journal for Humanities, 2025)
The Islamic Sharia is characterized by its consideration of the immediate and future interests of human beings. It is also distinguished from other systems by its harmony with innate human nature and sound intellect. Accordingly, its rulings—upon close examination—have taken these attributes into account. However, one may observe, in some juristic fatwas and intellectual opinions produced by the Muslim mind in specific eras and defined environments, a lack of alignment with these attributes and characteristics. These instances, upon reflection and contemplation, are few in proportion and number compared to the vast and noble Islamic heritage, yet they are worthy of study and reconsideration. Among such issues is the matter of guardianship of compulsion and the coercion of a woman into marriage. Although this view has been considered the predominant and majority opinion for centuries, in reality, it does not align with the objectives (maqāṣid) of the Sharia and its foundational principles, nor with the specific and established evidences related to the matter of marriage and its guardianship. Hence, the idea of this research emerged to shed light on the theory of guardianship of compulsion and to critique it, relying on valid evidences and the objectives of Islamic law. Undoubtedly, marriage is among the divine laws of creation, one from which neither the human world nor the realms of animals and plants deviate. Almighty God says: “And of everything We created [in] pairs, that you may remember.” [Surah Adh-Dhariyat: Verse 49]. It is the law chosen by Allah, the Glorified and Exalted, for procreation and multiplication. God did not will that the human being—unlike other beings—should release his instincts without awareness, nor that the contact between male and female be chaotic and unregulated. Rather, He established a system that preserves lineage and safeguards human dignity. Thus, He made the union between man and woman a noble connection based on her consent, through a formal offer and acceptance as indicators of that consent—since marriage pertains to their future lives, and it cannot succeed without affection and mercy. There can be no affection in a marriage conducted without the consent of one of the parties. Among the forms of marriage that can be described as occurring without the consent of both or one of the parties—and lacking the love necessary for its continuation—is forcing a woman into marriage. It has been established that this type of marriage leads, in most cases, to negative consequences, complex problems, and severe injustice. Unfortunately, it has become common in some Muslim societies. Therefore, by the help and grace of Allah, we have resolved to address this topic by presenting the evidences of the various viewpoints and critiquing them in accordance with the legal principles and objectives of Islamic law.
Keywords: Guardianship; Compulsion; Scriptural Texts; Sharia; Jurisprudence